The pedagogy of the virus: what can one learn with Covid-19? (Olhar de Professor, 2021)
The complexity of the current context is one of the challenges of our newsroom in times ofuncertainty, in which the destructive advance of covid-19 in Brazil has been forcing Brazilian states to expandsocial isolation, closing schools and suspending classes in their territories. From the point of view of our article,one of the lessons to be learned concerns the impacts of Covid-19 on the different scales of the lived territory.The coronavirus pandemic reiterates the political and epistemic dimension of the investigation of the site,considering it an analytical and comprehensive density of training processes for children, youth and adults.Dialoging with Santos (1994) who, in his theoretical formulation about his existential epistemology, urges us tocarry out the exercise of studying what each place has to be unique, specific, different and original to understandhow the subjects act and produce ways of life, social relations and practices, including the right to school.
Keywords: Right to education. Popular Education. Higher Education